Investigasi Dampak Kualitas Layanan dan Nilai Peserta terhadap Kepuasan di PT Taspen (Persero): Peran Kepercayaan sebagai Mediator - Olivia Skye; Andi Trio Suroso (Jurnal Bisnis Kreatif dan Inovatif, 2024)
This research aims to investigate the impact of service quality and participant value on participant satisfaction at PT Taspen (Persero), with a focus on the role of trust as a mediator. The research method uses a quantitative approach by collecting data through questionnaires distributed to PT Taspen participants. Data analysis was carried out using regression techniques to test the relationship between service quality variables and participants' scores on satisfaction, while mediation analysis was carried out to test the role of trust in connecting these variables. It is hoped that the research results will provide insight for PT Taspen in improving service strategies and participant value to increase participant satisfaction.